Influence of air distribution on combustion characteristics of a micro gas turbine fuelled by hydrogen-doped methane. (May 2022) - Lu, Jin; Fu, Zaiguo; Liu, Jiang; Pan, Weiguo
Abstract: Adding hydrogen to the fuel can change the combustion characteristics and greatly improve the pollutants emission for the gas turbine. The numerical method was adopted to study the combustion process in a counter-flow combustor of a 100 kW micro gas turbine using methane doped by hydrogen and various distribution schemes of air flow. The combustion characteristics and pollutant emissions were explored to ascertain the influence of air distribution based on solving the validated models. It was shown that as the amount of premixed air increased in the swirling gas, the range of the recirculation region became larger and the range of the high-temperature zone in the combustion chamber gradually enlarged. When the amount of premixed air was 30%, the outlet temperature distribution of the combustor was excellent and the average temperature was 1172 K. Moreover, the concentration of NO X gradually increased and reached a maximum value of 23.46 ppm (@15% O 2 ) as the premixed air increased in the range of the ratio less than 40%. It was reduced to 0.717 ppm (@15% O 2 ) when the amount of premixed air increased to 50%. These findings may support the running of the micro gas turbine using the hybrid fuel of hydrogen and methane.